Lessons with clay : step-by-step techniques for colorful designs in hand-thrown and handbuilt tableware - Dora, Melisa (Schiffer Publishing, 2022)
"Have you ever wanted to create your own ceramics but had no idea how to begin? Expert ceramicist Melisa Dora teaches you everything you need to know to make exquisite ceramic tableware. Step-by-step instructions clearly outline the techniques for forming and building your pieces, throwing the clay, firing, and glazing..."--